Uji Efek Penyembuhan Luka Sayat pada Kelinci (Oryctolagus cuniculus) Menggunakan Getah Jarak Pagar (Jathropha curcas L.) dalam Bentuk Sediaan Gel: The Healing effects of Cuts in Rabbit (Oryctolagus cuniculus) using Jatropha curcas L. in Gel - Izal Zahran; Murni Mursyid; Hurria Hurria (Jurnal Surya Medika (JSM), 2022)
The wound is defined as a breakdown of the epithelial integrity of the skin, which can be caused by sharp or blunt trauma, temperature changes, chemicals, explosions, electric shocks, or animal bites. Jatropha sap (Jatropha cuniculus L.) contains tannins and saponins that can stop bleeding, prevent infection, and play a role in wound healing. This study aims to determine whether the sap of Jatropha (Jatropha curcas L.) in the form of a gel can heal cuts and determine the concentration of jatropha sap in an effective gel formulation in healing cuts in experimental animals. The sap was collected and then formulated into a gel with concentrations of 15%, 20%, and 25%. The results showed that the gel formula with a concentration of 15% Jatropha gum could heal wounds for 18 days, a 20% concentration could heal wounds for 17 days, and a 25% concentration could heal wounds for 14 days. At the same time, the gel base cures for 19 days. From the research, it can be concluded that Jatropha (Jatropha curcas L.) latex in the form of a gel can provide the best healing effect at a concentration of 25% with the fastest wound healing time of 14 days.